The impact of CEFR implementation on language education in Malaysia - Panjalingam, Nesamalar (CELPAD Research Unit, CELPAD, International Islamic University Malaysia, 2023)
CEFR implementation in Malaysia in 2013 is a relatively new initiative by the Ministry of Education to elevate and improve the English language proficiency of Malaysian students. As usual with the implementation of something new, there were and still are many uncertainties of how it is to be carried out. This analytical research uses the findings and conclusions of other researchers and discusses the latest situation in schools and higher learning institutions with regards to the implementation of CEFR especially in Malaysia although what is happening in other countries is also discussed. This includes findings about the views of various parties as well as challenges faced by various stakeholders such as teachers and Ministry of Education officials. Some teachers are resistant to its implementation, while others do not have sufficient training and have negative understanding. Many teachers are of the view that it would be difficult to incorporate CEFR in their teaching. In Asian countries, there are also attempts to present alternative ways to use the framework to modify ELT. Many find the imprecision and open-endedness of CEFR troublesome although this very characteristic permits flexibility as per a particular context. To conclude, effective implementation of CEFR in Malaysia can be done if the key players involved are given adequate time and guidance.